Pemberian Alat Pengemasan dan Pelatihan Peningkatan Kualitas Makanan Khas Geti di Desa Purwosari Kabupaten Wonogiri - Nurafidah Nurafidah; Tegar Rezki Pangestu; Kris Suryowati; Rokhana Dwi Bekti (STAI Auliaurrasyidin Tembilahan, 2021)
There are so many types of traditional food in Indonesia that have a unique taste and characterize the local culture. However, nowadays many traditional specialties are still unable to compete with modern foods such as Geti Wijen. Some of the things that cause it are promotions that have not been widely used in various media and the appearance of packaging that is less attractive. One of the geti wijen businesses is Geti Mrs. Atmo in Dusun Geneng, Purwosari, Wonogieri District. This business has an unattractive packaging because the packaging process still uses simple tools and materials, namely plastic and wax. Therefore, the team provided a packaging tool assistance program and usage training to improve packaging quality. Implementation methods include planning activities, providing tools, implementing training, and evaluating programs. This program has provided many benefits for Mrs. Atmo in improving the quality of products that are able to compete in the market. Partners have packaging tools and attractive packaging designs so that the packaging process is faster.